Biorefinery synthesis and design using sustainability parameters and hierarchical/3D multi-objective optimization. (10th December 2019) - Meramo-Hurtado, Samir-Isaac; González-Delgado, Ángel-Darío
Abstract: Nowadays, there is demand to develop sustainable biorefineries that allow generation of a wide range of products, while reducing consumption of non-renewable resources. Such technologies can contribute to CO2 emission mitigation and improve energy efficiency. Thus, incorporation of sustainability parameters into process synthesis strategies has become increasingly important. Several renewable feedstocks and/or wastes are available for use as biofuels and as materials for pollution removal; this work presents a multi-objective optimization approach to biorefinery process synthesis that is based on sustainability parameters. The method presented here combined biorefinery synthesis and design through a hierarchical approach and mathematical programming and adopted simultaneous evaluation of economic, environmental, and exergy parameters. The methodology applied top-level decision-making, multi-objective optimization, and numerical methods to develop optimal biorefinery topologies based on waste/feedstock and final product selection. The model has implied formulation of a superstructure that considers interactions between feedstock/chemical species and processing layers. A novel addition incorporating chemical exergy loss to assess chemical exergy destruction in a biorefinery has also been applied. The proposed method was then applied to a case study for a shrimp-exoskeleton-based biorefinery in which chitosan, chitin, and astaxanthin were considered as potential main products. Highlights: Astaxanthin production through extraction methods is economically unfeasible. Shrimp exoskeleton biorefineries with attractive annual revenue were synthesize. Economic objective is contradictory respect to the environmental performance. Exergetic objective broadens the possibilities of optimal biorefinery designs. Including a third parameter provides a more complex formulation in process synthesis.